Optimization of a polarizer based on a square waveguide with irises - Писарчук, Олексій Олександрович; Конрад, Тетяна Ігорівна (Science-based technologies, 2020)
The article proposes the technology of automated traffic control in a multimodal transport network. The technology differs in the formalization of the transport problem in a multicriteria form and is the result of a synergistic combination of infographic model of factors, indicators, and criteria of route optimality and mathematical model of multicriteria distribution of traffic flows, which ensures the procedure of choosing the optimal route. The technology of automated traffic flow management in a multimodal transport network is based on the method of multicriteria selection of the optimal route of cargo transportation and the method of the optimal distribution of limited resources. The method of multicriteria selection of the optimal route of cargo transportation in a multimodal transport network is designed to implement the task of choosing the optimal route of cargo delivery in a multimodal transport network. The methodology is based on the presentation of the problem in a multicriteria form using a nonlinear scheme of compromises. The method of the optimal distribution of limited resources is designed for users (consumers) of transport services - shippers, passengers and provides for the implementation of the task of allocating the optimal route on the priority of customer service. The methodology is based on the use of a multicriteria optimization model obtained using nested convolutions according to a nonlinear scheme of trade-offs, which ensures that a significant number of criteria requirements, diversity of consumer needs (shippers, passengers), and limited resources (routes) are taken into account. The implementation of the technology involves the use of software and hardware complexes of interacting modes of transport through the introduction of a software system of multicriteria distribution of traffic flows. The structure of the software system of multicriteria distribution of traffic flows in a multimodal transport network contains the following blocks: database, knowledge base, algorithm-dispatcher, computational algorithm, training unit, information exchange system, and information display unit. The technology allows increasing the efficiency of traffic flow management in terms of efficiency and reliability of initial solutions.